Diversity in the pathway from medical student to specialist in the Netherlands: a retrospective cohort studyResearch in context - Lianne Mulder; Anouk Wouters; Eddymurphy U. Akwiwu; Andries S. Koster; Jan Hindrik Ravesloot; Saskia M. Peerdeman; Mahdi Salih; Gerda Croiset; Rashmi A. Kusurkar (Elsevier, 2023)
Summary: Background: Medical specialist workforces are not representative of the society they serve, partially due to loss of diversity in the path from student to specialist. We investigated which demographic characteristics of bachelor students of medicine (BSM) are associated with becoming a physician and (particular type of) medical specialist; and whether this suggests 'cloning' (reproduction of sameness) of the existing workforce. Methods: We used a retrospective cohort design, based on Statistics Netherlands data of all first-year BSM in 2002-2004 in The Netherlands (N = 4503). We used logistic regression to analyze the impact of sex, migration background, urbanity of residence, parental income and assets categories, and having healthcare professional parents, on being registered as physician or medical specialist in 2021. We compared our results to the national pool of physicians (N = 76,845) and medical specialists (N = 49,956) to identify cloning patterns based on Essed's cultural cloning theory. Findings: Female students had higher odds of becoming a physician (OR 1.87 [1.53-2.28], p < 0.001). Physicians with a migration background other than Turkish, Moroccan, Surinamese, Dutch Caribbean or Indonesian (TMSDI) had lower odds of becoming a specialist (OR 0.55 [0.43-0.71], p < 0.001). This was not significant for TMSDI physicians (OR 0.74 [0.54-1.03], p = 0.073). We found a cloning pattern with regard to sex and migration background. Nationwide, physicians with a Turkish or Moroccan migration background, and female physicians with other migration backgrounds, are least likely to be a medical specialist. Interpretation: In light of equity in healthcare systems, we recommend that every recruitment body increases the representativeness of their particular specialist workforce. Funding: ODISSEI.